AKTIVITAS ANTIOKSIDAN, SIFAT FISIK DAN SENSORI ES KRIM VANILA DENGAN PENAMBAHAN BUNGA TELANG (Clitoria ternatea L.) - Muzaifa, Murna; Widayat, Heru Prono; Nilda, Cut; Rahmi, Faidha (Jurnal Agroindustri, 2024)
Clitoria ternatea L.  flower with an attractive bright blue color possible as an alternative to natural dyes. This study aims to evaluate the effect of addition vanilla and telang flower extract to quality characteristics of ice cream. The research design used two factors, the type of vanilla (N1 = vanilla powder and N2 = liquid vanilla) and the concentration of telang flower extract (A1 = 0%, A2 = 15% and A3 = 30%). The addition of telang flower extract affects the antioxidant activity, melting time and hedonic color of the ice cream. The higher the telang flower extract added, the higher the antioxidant activity and preference for color but decreased the melting time of the ice cream. The melting time did not meet SNI No. 01-3713-1995. The type of vanilla affects the overrun value and texture of hedonic ice cream. The use of liquid vanilla provides an overrun value that is in accordance with the home industry ice cream standard with a preferred texture. Based on the overall characteristics, the best ice cream was obtained by using liquid vanilla and 30% telang flower extract. Further research is needed to optimize the melting time of the ice cream.